2014
DOI: 10.1002/dev.21218
|View full text |Cite
|
Sign up to set email alerts
|

Bdnf DNA methylation modifications in the hippocampus and amygdala of male and female rats exposed to different caregiving environments outside the homecage

Abstract: We have previously shown in infant rats that brief and repeated experiences with a stressed dam outside the homecage (maltreatment) alters methylation of DNA associated with the brain-derived neurotrophic factor (bdnf) gene within the developing and adult prefrontal cortex. BDNF is a key mediator of activity-dependent processes that have a profound influence on neural development and plasticity. Here we examined whether maltreatment also alters bdnf DNA methylation in two additional regions known to be promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 53 publications
11
101
0
Order By: Relevance
“…Within the amygdala, abuse-exposure is associated with decreased BDNF promoter I DNA methylation in females and decreased Bdnf promoter IV DNA methylation in males. However, in adulthood the direction of effect of abusive care on Bdnf DNA methylation in the hippocampus and amygdala suggests dynamic epigenetic changes occurring across the lifespan [117]. This phenomenon is consistent with observed biphasic responses in studies of early life adversity and expression of the Bdnf gene [118].…”
Section: Mechanistic Pathways Linking Maternal Care To Offspring Osupporting
confidence: 61%
See 1 more Smart Citation
“…Within the amygdala, abuse-exposure is associated with decreased BDNF promoter I DNA methylation in females and decreased Bdnf promoter IV DNA methylation in males. However, in adulthood the direction of effect of abusive care on Bdnf DNA methylation in the hippocampus and amygdala suggests dynamic epigenetic changes occurring across the lifespan [117]. This phenomenon is consistent with observed biphasic responses in studies of early life adversity and expression of the Bdnf gene [118].…”
Section: Mechanistic Pathways Linking Maternal Care To Offspring Osupporting
confidence: 61%
“…In adulthood, both males and females are observed to have increased DNA methylation in Bdnf promoter I in the prefrontal cortex, but at promoter IV only abuse-exposed females are observed to have increased DNA methylation [116]. At PND 8, abuse-exposed females have increased DNA methylation of Bdnf promoter IV in the ventral hippocampus [117]. Within the amygdala, abuse-exposure is associated with decreased BDNF promoter I DNA methylation in females and decreased Bdnf promoter IV DNA methylation in males.…”
Section: Mechanistic Pathways Linking Maternal Care To Offspring Omentioning
confidence: 99%
“…Epigenetic regulation at specific BDNF promoters has been correlated with impaired fear regulation and anxiety [47,48]. Early exposure to adverse events results in chromatin remodeling that influences BDNF expression in regions important for fear regulation and anxiety during adulthood [49,50]. At the genetic level, a single-nucleotide polymorphism (SNP) at BDNF codon 66 is implicated in fear regulation and anxiety [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the effect of the Val66Met SNP on neuronal development and regulated release of BDNF (Chen et al, 2006;Egan et al, 2003), a knock-in mice carrying the BDNF Val66Met SNP (BDNF Met/Met ) showed an impairment of synaptic plasticity in the mPFC and hippocampus, which might interfere with the top-down control of the amygdala, a mechanism necessary for fear regulation (Bath et al, 2012;Ninan, 2014;Ninan et al, 2010;Pattwell et al, 2012a). However, given the role of BDNF in amygdala plasticity (Rattiner et al, 2005;Rosas-Vidal et al, 2014;Roth et al, 2014), it is also plausible that the BDNF Val66Met SNP exerts a direct effect on amygdala synapses. Human BDNF Val66Met carriers continued to recruit the amygdala despite fear extinction training, suggesting an altered amygdala plasticity (Soliman et al, 2010).…”
Section: Introductionmentioning
confidence: 86%